The Role of the Algerian Administrative Judge in Resolving Disputes Through Conciliation - Hennane, Aabdelhamid; Badir, Yahia (Journal of Legal Studies and Researches, 2024)
The Algerian legislature, through its authorization of administrative reconciliation and its confinement to the article of the full judiciary, aims at granting the judge broad authority in deciding on or rejecting the procedure of reconciliation, so that the judge plays a prominent role in provoking reconciliation, both on his own proposal and on the initiative of the adversaries, in view of its importance in reducing the burden on the courts.